PENGARUH KUALITAS PRODUK DAN REPUTASI MEREK TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN MIE INSTAN MEREK INDOMIE DI KOTA DENPASAR - Sanjaya, Wayan; Rahyuda, Ketut; Wardana, Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
Product quality and brand reputation are factors that determine customer satisfaction and loyalty in determining which products will be purchased or used so that product quality and brand reputation are key to the success of a company . The purpose of this study was to determine the effect of product quality to customer satisfaction brand Indomie instant noodle products in Denpasar, to determine the influence of the brand's reputation for customer satisfaction brand Indomie instant noodle products in Denpasar, and to determine customer satisfaction to customer loyalty brand instant noodle products Indomie in Denpasar. The population in this study are all Indomie instant noodle product users in the city of Denpasar . The sample scarried out by non-probability sampling techniques. The samples used as many as 160 respondents. The research data is primary data obtained through a questionnaire using Likert scale. Research hypothesis testing using SEM analysis techniques with tools AMOS. The results showed that : product quality and significant positive effect on customer satisfaction, brand reputation and significant positive effect on customer satisfaction, and customer satisfaction and significant positive effect on customer loyalty. Based on these results, the reputation of the brand Indomie instant noodles to note with regard to the benefits perceived by the customer, maximizing marketing through advertising and promotion.
Keywords: quality, reputation, satisfaction, loyalty